Reconstruction of Telemedicine Regulations In The Indonesian Health Legal System Based on A Legal Pluralism Approach - Hawreyvian Rianda Seputra; Setyarini; Yuswanti; Marsudi Dedi Putra (Journal of Law, Politic and Humanities, 2026)
This research aims to analyze the urgency of reconstructing telemedicine regulations in Indonesia using the legal pluralism approach to create legal certainty that is adaptive to the development of digital health technology. The research method applied is normative law with a focus on the analysis of legal texts, laws and regulations, doctrines, and scientific publications related to the health legal system. Literature studies are used as a secondary data collection technique to map the current legal position as well as existing legislative gaps in the practice of remote health services. Qualitative juridical analysis was carried out to formulate normative solutions to strengthen the legal framework of telemedicine to suit the characteristics of legal science and social realities in Indonesia. The results of the study show that the current telemedicine regulations, including Law Number 17 of 2023 concerning Health, Government Regulation Number 28 of 2024, and Permenkes Number 20 of 2019, are still global and delegative, causing uncertainty at the operational technical level. The absence of specific norms regarding remote diagnostic standards, remote therapy procedures, and limitations on non-face-to-face medical measures increases the risk of malpractice and uncertainty of the legal liability of health workers. The protection of patients' personal data has also not been regulated in detail, especially regarding the security mechanism for sensitive medical data and reporting obligations in the event of a digital information breach. Regulatory reconstruction based on legal pluralism is needed to integrate formal positive law, medical professional ethics, and information technology law into one harmonious legal system. Standardization that includes consultation procedures, electronic prescriptions, and effective supervision mechanisms will provide balanced legal protection for patients, medical personnel, and digital platform operators. Adaptive and flexible arrangements ensure that the law remains relevant to technological innovation without compromising the principles of justice and public safety.